SnO2@N‐Doped Carbon Hollow Nanoclusters for Advanced Lithium‐Ion Battery Anodes. Issue 6 (12th January 2016) - Li, Lu; Zhang, Lingyu; Chai, Fang; Wang, Tingting; Li, Zilu; Xie, Haiming; Wang, Chungang; Su, Zhongmin
Abstract: A facile method to synthesize novel monodispersed SnO2 @N‐doped carbon hollow nanoclusters as a high‐performance anode material for lithium‐ion batteries was explored. The uniqueness of this structure results from the large amount of ultrafine small SnO2 nanoparticles, the hollow interior space, and the continuous N‐doped carbon shells, which successfully buffer problems associated with huge volume changes and guarantee electrical connectivity. All of these features make the nanocomposite well fitted for lithium storage. As a result, the electrochemical performance of monodispersed SnO2 @N‐doped carbon hollow nanoclusters as an anode in lithium‐ion batteries is significantly improved, as it shows high initial discharge and charge capacities of 1572 and 1003 mA h g –1, respectively. Importantly, nearly 100 % discharge/charge efficiency is maintained during 100 consecutive cycles with a specific capacity above 910 mA h g –1 . Abstract : A unique functional nanoarchitecture, SnO2 @N‐doped carbon hollow nanoclusters, consisting of a large amount of ultrafine small SnO2 nanoparticles, a hollow interior space, and continuous N‐doped carbon shells is fabricated. This material shows highly reversible lithium storage and outstanding cycling performance as an anode material for lithium‐ion batteries.